Tourist satisfaction towards tourism facilities provided in the urban tourism area, Ipoh, Malaysia - Nik Aisyah binti Nik Marzuki (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
Tourism industry consists of firms, organizations and facilities that are intended to serve the specific needs and wants of the tourists. Poor and dearth of tourism facility management lead to the declining number of tourists, as without tourist satisfaction in the use of facilities and amenities cause a poor destination loyalty in the tourism destination. This research is focusing on Ipoh, the capital city of Perak due its potential, as there are a variety of attractions and tourism products that can attract a lot of tourists. The main objective of this research is to examine the tourist satisfaction level towards tourism facilities provided at urban tourism destination in Ipoh. The focus of this research is to identify the demographic data of the tourist, identify the tourism facilities provided, evaluate tourists' satisfaction and suggest the possible recommendation to improve the current tourism facilities in the study area. The questionnaire survey is used as the main tool to examine the satisfaction level of tourists and it was distributed to a total of 100 tourists from other places including domestic and international visitors. Likert Scale and Relative Importance Index (RII) are used to ascertain the rate of the tourism facilities provided, depending on their satisfaction rank. Spearman Rho's Correlation is also used as a tool to evaluate the relationship between the variables. The outcome of the research shows that the tourists are not satisfied with several tourism facilities based on the result of the RII calculation. There are three tourism facilities that have the lowest satisfaction level among the tourist which are public toilet ranked number 10 with RII 0.624, transportation ranked number 9 with RII 0.652 and supporting facilities ranked number 8 with RII 0.588. The outcome and suggestion of this research will help the local authority and non-government agencies to improve the existing tourism facilities in order to achieve high satisfaction level among the tourists in the study area.